2020
DOI: 10.1186/s13017-020-00325-0
|View full text |Cite
|
Sign up to set email alerts
|

Training to identify red flags in the acute care of trauma: who are the patients at risk for early death despite a relatively good prognosis? An analysis from the TraumaRegister DGU®

Abstract: Background: In the acute care of trauma, some patients with a low estimated risk of death die suddenly and unexpectedly. In this study, we aim to identify predictors for early death within 24 h following hospital admission in low-risk patients. Methods: The TraumaRegister DGU® was used to collect records of patients who were primarily treated in a participating hospital between 2004 and 2013 with a RISC II score below 10%. Results: During the study period, 64,379 patients met the inclusion criteria. The mean R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…7,[9][10][11][12][13][14][15] Recently it was demonstrated that severe thoracic trauma is associated with a higher risk of death within the first 24 h in patients with a low estimated risk of death. 16 These patients' likelihood of independent survival improves with early diagnoses and subsequent resuscitative interventions. 10,13 Early life-saving interventions (LSI) for thoracic trauma include intubation/ventilation, pleural decompression, haemostatic transfusion and resuscitative thoracotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[9][10][11][12][13][14][15] Recently it was demonstrated that severe thoracic trauma is associated with a higher risk of death within the first 24 h in patients with a low estimated risk of death. 16 These patients' likelihood of independent survival improves with early diagnoses and subsequent resuscitative interventions. 10,13 Early life-saving interventions (LSI) for thoracic trauma include intubation/ventilation, pleural decompression, haemostatic transfusion and resuscitative thoracotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that severe thoracic trauma is associated with a higher risk of death within the first 24 h in patients with a low estimated risk of death. 16 These patients’ likelihood of independent survival improves with early diagnoses and subsequent resuscitative interventions. 10 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…2 Some previous studies on adult trauma reported that vital signs, the state of consciousness, and comorbidities which were not treated in time were risk factors worthy of attention. [3][4][5][6] However, the study is limited by its retrospective design and missing data (7.36%). A large-scale, multi-center, prospective study is needed to evaluate its effectiveness and capability further.…”
mentioning
confidence: 99%